Contribution of External Public Relations of Directorate General of Tax Through social media to the Organizational Image and the Increase in Tax Awareness - Tengku Amiliza; Hendra Harahap; Syafruddin Pohan (Budapest International Research and Critics University, 2022)
The objective of the research is to evaluate whether social media of the Ditjen Pajak (Directorate General of Tax) has contribution to the organizational image and the increase in tax awareness and to analyze whether the contribution is different between its heavy followers and light followers. The theory used is 4C theory in using social media: context, communication, collaboration, and connection. The population is the followers of facebook account and instagram and non-tax employees of the Ditjen Pajak. The samples are 200, taken by using purposive sampling, based on the result of observation, and accidental sampling technique. The result of testing using the SPSS program with linear regression analysis and Spearman Rho-Rank correlation test, shows that there is contribution of social media at the Ditjen Pajak to the organizational image with a quite meaningful correlation in the two variables and there is contribution of social media at the Ditjen Pajak to tax awareness with insignificant but positive correlation in the two variables. The result of Chow test indicates that there is a difference in the contribution of social media at the Ditjen Pajak to its image between its heavy followers and light followers, but there is no difference in the contribution of social media at the Ditjen Pajak to tax awareness between its heavy followers and light followers.